On-farm greenhouse gas emissions associated with the cultivation of two new bioenergy crops in the UK - Cumplido-Marin, Laura; Graves, Anil; Burgess, Paul J.; Williams, Adrian (Elsevier, 2022)
Before using novel energy crops to produce bioenergy, feasibility studies should be completed to determine their effect on net greenhouse gas emissions. The current study developed a model to study the greenhouse gas emissions associated with the cultivation of two novel bioenergy crops: Sida hermaphrodita (L.) Rusby and Silphium perfoliatum L., using Intergovernmental Panel on Climate Change (IPCC) guidelines. The establishment and cultivation of Sida hermaphrodita and Silphium perfoliatum were compared with an arable rotation, short rotation coppice (SRC) and Miscanthus. Under the assumptions specified in the current study, including annual fertilisation and a high root: shoot ratio for Sida, the cultivation of Sida hermaphrodita and Silphium perfoliatum resulted in a mean net emission of 3.0 Mg CO2eq ha−1y−1 and mean net sequestration of 0.6 Mg CO2eq ha−1y−1 respectively over a 16 year rotation. This compared to predicted mean net emissions of 4.2 Mg CO2eq ha−1y−1 for an arable rotation, and intermediate values for the SRC and Miscanthus crop (1.0 and 2.2 Mg CO2eq ha− 1y− 1, respectively).
Keywords: Cup plant; Virginia fanpetals; Virginia mallow; greenhouse gas emissions; bioenergy crops